Effect of Silica and Tin Oxide Nanoparticles on Properties of Nanofibrous Electrospun Separators. Issue 6 (1st January 2015) - Zaccaria, M.; Fabiani, D.; Cannucciari, G.; Gualandi, C.; Focarete, M. L.; Arbizzani, C.; De Giorgio, F.; Mastragostino, M.
Abstract : Innovative separators able to improve the performance and safety of Li-ion batteries are under investigation to meet the growing demand for large-size and high energy density electrochemical cells. In this work, highly porous nanofibrous Poly(vinylidene fluoride) (PVdF) separators loaded with oxide nanoparticles were produced by electrospinning. Silicon oxide and tin oxide nanoparticles were added to PVdF and membranes were characterized by SEM-EDS and TGA. The effect of nanoparticle addition on electrolyte uptake, mechanical properties and conductivity was investigated and such properties were compared to those of a commercial separator (Celgard 2400). Results showed that a small amount of additive can significantly improve the properties of PVdF electrospun membranes and that the different nanoparticles investigated in this work have different effect on membrane performances. In particular, the addition of SiO2 increases the rate of electrolyte uptake and the toughness of the electrospun membrane, while the addition of SnO2 decreases the rate of electrolyte uptake and increases the stiffness of the electrospun membrane. When loaded with nanoparticles, PVdF membranes maintain their insulating character also at high temperature. Preliminary electrochemical results on half-cell vs Li with LiFePO4 and electrospun separators showed good cycling performance, highlighting interesting features of this technology.